Stress-strain based method for analysis and design of FRP wrapped reinforced concrete columns. (December 2020) - NadimiShahraki, Kourosh; Reisi, Mohammad
Abstract: Wrapping reinforced concrete (RC) column with FRP sheets enhances compressive strength and ductility of column. Since stress–strain curve of FRP-strengthened concrete is different from stress-strain curve of normal (un-strengthened) concrete, relations presented by codes to design and analysis of normal column and based on stress–strain curve of normal concrete cannot be used for design and analysis of FRP-strengthened concrete. In this research, the feasibility of using the stress–strain curve of FRP confined concrete for analysis and design of FRP wrapped RC columns has been investigated. To do so, stress–strain curve of confined concrete presented by researchers and ACI code was used to design an algorithm for determination axial and bending capacity (uniaxial and biaxial) of RC strengthened columns with rectangular and circular sections. The algorithm was implemented in Visual C#. Then, verification of this method was confirmed by comparing the result of this method to experimental results. Verification results showed that stress–strain based method can predict axial and bending capacity of strengthened columns properly. A common and simple method used for designing FRP- strengthened RC columns is based only on controlling compressive strength. This means that if a FRP wrapped concrete can provide required compressive strength, strengthening of column is confirmed and this issue that stress–strain curve of normal column is different from stress-strain curve of confined concrete, is neglected. Hence, this designing method was also verified by programing in this study. Results revealed that the designing method can be used prudently.